การสะสม การเคลื่อนย้าย และผลกระทบของอนุภาคเงินนาโนที่มีต่อข้าวหอมมะลิ 105 ข้าวเหนียว กข 6 และผักบุ้งจีน - คัญทัพ, จักรกริสน์; วะสุกัน, นุจรินทร์; ศรีสังข์, สุจิตรา (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2020)
ปัจจุบันประเทศไทยมีการใช้อนุภาคเงินนาโนกันอย่างแพร่หลาย ด้วยคุณสมบัติของอนุภาคเงินนาโนที่มีสมบัติเป็นสารต้านเชื้อแบคทีเรียและเชื้อราในการเกษตร ซึ่งอนุภาคเงินนาโนอาจมีโอกาสปลดปล่อยสู่สิ่งแวดล้อมและส่งผลกระทบต่อพืชในเกษตรกรรม งานวิจัยนี้จึงมีวัตถุประสงค์เพื่อศึกษาผลของอนุภาคเงินนาโนต่อการสะสม การเคลื่อนย้าย และผลกระทบในพืช 3 ชนิด ได้แก่ ข้าวหอมมะลิ 105 ข้าวเหนียว กข6 และผักบุ้งจีน ในการทดลองขั้นตอนแรกได้ทำการสังเคราะห์อนุภาคเงินนาโนโดยใช้น้ำผึ้งธรรมชาติเป็นตัวรีดิวซ์ นอกจากนี้ศึกษาเปรียบเทียบกระบวนการย่อยแบบเปียก 3 วิธีคือ วิธี D1 D2 และ D3 เมื่อพืชทั้ง 3 ชนิด ได้รับสัมผัสกับอนุภาคเงินนาโนที่ความเข้มข้น 0.02, 0.05, 0.1 และ 1 มิลลิกรัมต่อลิตร แล้ววิเคราะห์หาปริมาณโดยเทคนิคแกรไฟต์เฟอร์เนซอะตอมมิกแอบซอร์ปชันสเปกโทรเมตรี ผลการทดลองพบว่า กระบวนการย่อยวิธี D2 เป็นกระบวนการย่อยที่เหมาะสม เนื่องจากผลของร้อยละการคืนกลับอยู่ระหว่างร้อยละ 81.67 - 94.00 ในขณะที่การศึกษาปริมาณการสะสม การเคลื่อนย้าย และการกระจายตัวของ อนุภาคเงินนาโนในส่วนต่างๆ ของพืช พบว่าข้าวเหนียว กข6 ในส่วนของรากที่สัมผัสกับอนุภาคเงินนาโนที่มีความเข้มข้นเท่ากับ 0.05 มิลลิกรัมต่อลิตร เกิดการรวมตัวและสะสมอยู่ผนังเซลล์ ภายในเซลล์ของรากส่งผลต่อการลำเลียงสารอาหาร และพัฒนาการเจริญเติบโตของเซลล์พืช คำสำคัญ: อนุภาคเงินนาโน ข้าวเจ้าหอมมะลิ 105 ข้าวเหนียว กข6 ผักบุ้งจีน การสะสม Currently, silver nanoparticles (AgNPs) are widely used in agriculture area due to their properties as anti-bacterial and fungi. AgNPs may be released into the environment and impacts on agricultural crops have been exposed. In this work, to investigate the effects of AgNPs, accumulate, translocation and impacts on three plants including rice (Oryza sativa L. cv. KDML 105), sticky rice (Oryza sativa var. glutinosa cv. RD 6) and Chinese water convolvulus (Ipomoea aquatic Forsk. Var. reptan) were studied. The AgNPs were synthesized by pure natural honey as a reducing agent. In addition, the wet digestion of D1, D2 and D3 methods for determination of silver accumulation were evaluated. The three plants were exposed to AgNPs with various concentrations of 0.02, 0.05, 0.1 and 1 mg/L. After wet digestion the silver concentration were determined by graphite furnace atomic absorption spectroscopy (GFAAS). The results showed that the D2 method was the optimum wet digestion process for the determination of silver in plants with the percent recovery of 81.67 to 94.00. The aggregation and accumulation of AgNPs within the roots and shoots of three plants were found that the roots of sticky rice at a concentration of 0.05 mg/L and penetrated to the cell wall and cell in root leading to effects on structural features and transporting nutrients to the plants, including the development on the growth of plant cells. Keywords: Silver nanoparticles, Rice (Oryza sativa L.cv. KDML105), Sticky rice (Oryza sativa var. glutinosa cv. RD 6), Chinese water convolvulus (Ipomoea aquaticaForsk. Var. reptan), Accumulation